A mixed-method analysis of fraud awareness, fraud literacy, public service motivation, professional scepticism, and corruption - Maulidi, Ach (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
This study examines whether fraud awareness and fraud literacy reduce corrupt behaviour in public institutions and whether public service motivation and professional scepticism condition these relationships. Drawing on Social Exchange Theory, the study adopts an explanatory sequential mixed-method design. Quantitative data were collected from 137 employees of a local government institution in East Java and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). To complement the quantitative findings, qualitative data were subsequently gathered through semi-structured interviews with eight participants and analysed using thematic analysis. The quantitative results show that fraud awareness, fraud literacy, public service motivation, and professional scepticism do not have significant direct effects on corruption. However, the interaction effects are negative and significant. These suggest that fraud awareness and fraud literacy become behaviourally meaningful to prevent corruption when combined with public service motivation and professional scepticism that activate ethical responsibility within organisational relationships. Interestingly, the qualitative findings deepen this explanation by showing that employees interpret responsibility through shared decision structures, hierarchical relationships, and clearly defined role boundaries. These relational conditions shape how individuals translate knowledge of fraud risks into ethical actions in everyday administrative work. Although this study is conducted in the public sector, its insights extend to private sector governance as well. For instance, this perspective enriches existing fraud prevention research by highlighting how knowledge-based capacities interact with motivational and professional orientations to shape integrity outcomes across different organisational contexts.